1993
DOI: 10.1364/josaa.10.001792
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal comparison of temporal-modulation perimetry with white-on-white and blue-on-yellow perimetry in ocular hypertension and early glaucoma

Abstract: We obtained data over 3 years on temporal-modulation perimetry (TMP), standard automated [white-on-white (W/W)] perimetry, and short-wavelength-sensitive [blue-on-yellow (B/Y)] perimetry in ocular hypertensive (OH) patients and patients with early glaucomatous visual-field loss (EG). Evidence of visual-field defects was obtained with the use of both B/Y perimetry and TMP in the majority of OH and EG eyes that demonstrated progression on W/W perimetry as well as in all stable EG eyes. Using the nerve-fiber-bund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0
2

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 15 publications
4
44
0
2
Order By: Relevance
“…Short-wavelength automated perimetry test locations corresponding to each of the 14 psample@eyecenter, ucsd. edu).…”
mentioning
confidence: 99%
“…Short-wavelength automated perimetry test locations corresponding to each of the 14 psample@eyecenter, ucsd. edu).…”
mentioning
confidence: 99%
“…Cross-sectional and longitudinal investigations from these laboratories were able to establish that SWAP was capable of characterizing glaucomatous visual field defect patterns, [50][51][52][53][60][61][62][63][64] could detect glaucomatous visual field loss up to 10 years earlier than standard perimetric testing, 70 could predict future glaucomatous damage on conventional perimetric testing, [55][56][57][60][61][62][63][64][65][66] and was able to determine a greater amount of progressive glaucomatous loss as compared to standard perimetric testing. 52,55,61,68 A collaborative study was able to determine the optimal clinical test procedures for SWAP, which consisted of a highluminance (100 cd/m 2 ) broadband yellow background with a dominant wavelength of 530 nm (OG 530 Kodak Wratten filter), a narrow band (10 nm) large (Goldmann Size V) "blue" stimulus (dominant wavelength of 440 nm, Omega filter) presented for 200 ms. 54 These conditions were able to minimize the effect of lens attenuation of short wavelength light, maximize the dynamic range of SWAP, and provide the greatest amount of isolation of short wavelength sensitive mechanisms. Subsequent investigations were able to adapt Bayesian forecasting test procedures to SWAP to diminish testing time to 3-4 min per eye, expand the dynamic range by more than 4 dB, and slightly reduce variability while…”
Section: Short Wavelength Automated Perimetrymentioning
confidence: 99%
“…119 Both of these procedures have been used effectively in the detection of glaucomatous visual field loss and have demonstrated the ability to provide earlier detection of damage and the ability to predict future loss using standard automated perimetry tests. 68,[119][120][121][122][123][124][125] A direct comparison of the two procedures that tested the same normal controls and glaucoma patients using both techniques suggested that temporal modulation perimetry provided slightly better separation of results from normal control subjects in comparison to glaucoma patients. 119 Although it has been reported that high temporal frequencies provide the best results, 121 more recent studies have not found a particular preference for any temporal frequency.…”
Section: Flicker Perimetrymentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20] While the original premise for developing tasks that assess the M and K pathways is not supported by recent literature, this does not detract from the clinical utility of these tests, which have been shown to detect glaucomatous visual field loss earlier than standard white-on-white perimetry. [21][22][23][24][25][26] More recently, it has been proposed that the ability of tasks that assess M and K pathway function to more readily detect early visual field loss may arise from the minimal neural redundancy in these pathways. 27 There are far fewer M-and K-neurons than P (the retinal ganglion cell population comprises approximately 80 per cent P, 10 per cent M and five to 10 per cent K), hence M and K cells are sparsely distributed.…”
Section: Alternate Stimulus Types To Standard White-on-white Luminancmentioning
confidence: 99%